2016
DOI: 10.1155/2016/8793095
|View full text |Cite
|
Sign up to set email alerts
|

ESP‐102, a Combined Herbal Extract of Angelica gigas, Saururus chinensis, and Schisandra chinensis, Changes Synaptic Plasticity and Attenuates Scopolamine‐Induced Memory Impairment in Rat Hippocampus Tissue

Abstract: ESP-102, an extract from Angelica gigas, Saururus chinensis, and Schisandra chinensis, has been used as herbal medicine and dietary supplement in Korea. Despite the numerous bioactivities in vitro and in vivo studies, its effects on neuronal networks remain elusive. To address the neuronal effect, we examined synaptic plasticity in organotypic hippocampal slice culture with multielectrode array. Our results showed an increase in excitatory postsynaptic potential (EPSP), indicating the induction of long-term po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Kim et al . found that ESP-102 treatment significantly increases LTP induction in the hippocampal slice, and can also recover the scopolamine-suppressed BDNF and GluR2 protein levels, suggesting that ESP-102 is a novel herbal ingredient with memory-enhancing as well as neuroprotective effects [ 100 ]. As stated above, Rg1, which prevents glutamate-induced neuronal death, might not act by antagonizing NMDA receptors [ 81 ].…”
Section: Regulation Of Glutamate-mediated Signaling By the Natural Comentioning
confidence: 99%
“…Kim et al . found that ESP-102 treatment significantly increases LTP induction in the hippocampal slice, and can also recover the scopolamine-suppressed BDNF and GluR2 protein levels, suggesting that ESP-102 is a novel herbal ingredient with memory-enhancing as well as neuroprotective effects [ 100 ]. As stated above, Rg1, which prevents glutamate-induced neuronal death, might not act by antagonizing NMDA receptors [ 81 ].…”
Section: Regulation Of Glutamate-mediated Signaling By the Natural Comentioning
confidence: 99%
“…Furthermore, ESP-102 controlled the loss of mitochondrial membrane potential in glutamate-induced rat cortical cells. Recently, the neuroprotective effect of ESP-102 against scopolamine-induced toxicity in rat hippocampal slice was studied by Kim et al [ 34 ]. The results showed that ESP-102 competitively antagonized the preventative long-term potentiation effect in the scopolamine-induced hippocampal slice.…”
Section: Neuroprotective Properties Of a Gigas mentioning
confidence: 99%
“…Sauchinone, a biologically active lignan isolated from the aerial parts of S. chinensis , also shows anti-oxidative, anti-inflammatory, hepatoprotective, anti-cardiovascular, anti-obesity, and anti-hepatic steatosis activities [ 17 , 18 , 19 , 20 , 21 , 22 ]. Recently, the approval of ESP-102 as a functional food containing sauchinone from S. chinensis (Daewoong Bio, South Korea; [ 17 ]) shows that S. chinensis can be developed as a source of functional food or herbal medicine in combination therapies [ 18 , 19 , 20 , 21 , 22 ]. As a major component of S. chinensis , sauchinone is extensively metabolized via CYPs and is highly distributed in the liver [ 23 ], suggesting that sauchinone–drug interaction may occur via CYP inhibition.…”
Section: Introductionmentioning
confidence: 99%